Experiences of dental students in virtual education: A qualitative study - Neda Yasamineh; Mina Hosseinzadeh; Reza Ghaffari; Seyed Gholamreza Noorazar; Katayoun Katebi; Mohammad Said Khodayi (Research and Development in Medical Education, 2024)
Background: Virtual education, adopted and utilized as a reaction to global changes, has brought about challenges and opportunities to many medical schools worldwide. This study aimed to shed light on the experiences of dental students with virtual learning in theoretical courses. Methods: This qualitative-descriptive study was conducted in 2022 using semi-structured interviews with open-ended questions. The 15 interviewees were selected purposively and based on theoretical methods to obtain the most information. The interviews were analyzed using the conventional qualitative content analysis method. MAXQDA version 11 software was used for open coding and categorizing codes. Results: Two main categories (themes) were obtained under the headings of perceived disadvantages and perceived advantages of virtual education. From the perspective of students, the disadvantages of virtual education were categorized into 10 sub-themes such as infrastructure problems and low interaction, and its advantages were categorized into 5 basic concepts such as ease of access to faculty and students and flexibility in training time. 145 open codes were primarily extracted from interviews. Conclusion: Online learning due to the conditions of nowadays world and the occurrence of extensive changes, including biological crises such as the COVID-19 pandemic, has encountered some advantages and disadvantages. The inevitability of future threats, whether biological or man-made, accentuates the importance of studies like this. Such research can be of interest to policymakers and educational administrators in assessing the effectiveness of education in similar conditions future.